Elements of Promotion Mix and Their Effect in Insurance Service Marketing by Using Factor Analysis Approach: An Exploratory Research foe views of works Sample at the National Insurance Company (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The insurance is considered as one of the sectors that is impact is vital to the national economy and development programs, Insurance companies as financial institutions have an effect an aspects of social, economic as well as the participation of enterprises in compensation for the risk potential losses and individuals, Insurance sector provides insurance service insurance which should be characterized by quality and satisfy  needs and desires of the customer , so the  raise insurance awareness in the community its members and institutions will help in  maintaining the movement of production and service delivery standards, quality sought by the insured to obtain, as well as the development of promotional programs, and use of technology and technical means available to enable the company to achieve its objectives and also provide insurance. under, the Iraqi situation with economic transformation the requirements of market   economy and privatization. The insurance companies                                                                                     have to develop their promotional methods and disciplines, including  the working   methods and  disciplines ,including  the working staffs which can gain competitive advantages in the labor market. With the proliferation of media institutions and the different means methods of promotion and communication with the diversity of artistic techniques through which to view activities by all possible means and delivery to the beneficiary on different cultural levels, and the opening up of markets in light of market globalization, economics and information technology make the competition intensifies, which requires that working companies are seeking in the insurance sector to be a mix marketing and promotional language and style that fits with the size of the competition and th e nature of communities